2014
DOI: 10.2478/s11756-014-0340-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and geographic distribution of variation of Hordeum murinum as revealed by retroelement insertional polymorphisms in Iran

Abstract: Hordem murinum is a widespread weedy/wild species, growing in different ecological conditions in Iran. Populations of H. murinum subsp. glaucum (2n = 2x = 14) and subsp. leporinum (2n = 4x, 6x = 28, 42) are found in this region. Inter-retroelement amplified polymorphism (IRAP) markers were used to analyse the genetic diversity of 57 accessions of H. murinum from different regions of Iran, and to examine patterns of diversity related to the taxonomy and geography. Eight IRAP primer combinations amplified a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This grouping in the western accessions indicated the existence of three differentiated groups of colonies along the Zagros Mountains in Iran. Previous investigations into genetic diversity of other Poaceae taxa such as wild barley (Khodayari et al , 2014), Hordeum murinum (Sharifi-Rigi et al , 2014), diploid wheats (Naghavi et al , 2009; Mousavifard et al , 2015) and Secale spp. (Akhavan et al , 2010; Jenabi et al , 2011) also showed high variability in germplasms that originated from the Zagros Mountains in the west of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…This grouping in the western accessions indicated the existence of three differentiated groups of colonies along the Zagros Mountains in Iran. Previous investigations into genetic diversity of other Poaceae taxa such as wild barley (Khodayari et al , 2014), Hordeum murinum (Sharifi-Rigi et al , 2014), diploid wheats (Naghavi et al , 2009; Mousavifard et al , 2015) and Secale spp. (Akhavan et al , 2010; Jenabi et al , 2011) also showed high variability in germplasms that originated from the Zagros Mountains in the west of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to the SRAP markers, REMAP markers could be related to the geographical origin of this species. Many studies have reported that retrotransposon-related polymorphism is associated to the evolution events in species (Kalendar et al, 1999;Basirnia et al, 2014) and to their geographical origin (Sharifi-Rigi et al, 2014). Indeed, the REMAP markers used in this study have divided C. scorpioides by their evolutionary rate.…”
Section: Discussionmentioning
confidence: 92%
“…Our results show that hare barley displayed not only a remarkable phenotypic plasticity but also a high epigenetic diversity in response to increased temperature, decreased rainfall and the combination of both. Global methylation seems to be widely generalised in the genome of many plant species (Suzuki et al 2008 ), being particularly frequent in species with high presence of transposable elements such as hare barley (Jakob et al 2004 ; Sharifi-Rigi et al 2014 ), and large genomes such as Zea mays (Diez et al 2014 ). Specifically, our study species was found to have the largest genome within the Hordeum genus (Jakob et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%